Private equity : a new popular investment tool (case study of emerging markets) - Tan, Qian Wen. (2009)
Private equity is an alternative investment vehicle that has been gaining popularity in recent years due to its capability to generate remarkably high returns. This report seeks to understand the workings of PE and analyze the investing environment of new emerging markets, especially Brazil, Russia, India and China that have captured the interest of both investors and companies. PE refers to equity capitals that are not listed publicly on exchanges. PE funds are invested commonly in venture projects and Merger & Acquisition. US is an ideal place for PE investments due to its developed PE infrastructure. However, due to the negative effects of the recent credit crunch, investors’ attention was shifted to the emerging markets instead. Analyzing the opportunities and pitfalls of the investing environment of these markets gives investors an insight to the markets to make better decision. Given the ongoing changes in its investing environment, the emerging markets look set to capture majority of the PE funds in the world in the future.